Rutherford visits middle school: a case study on how teachers direct attention to the nature of science through a storytelling approach. (15th April 2019) - Hansson, Lena; Arvidsson, Åsa; Heering, Peter; Pendrill, Ann-Marie
Abstract: It has long been argued that nature of science (NOS) is an important part of science teaching. In the literature, many different approaches to NOS have been suggested. This article focuses on a storytelling approach, and builds on data from audio recordings from three middle-school (school year 6) classrooms. The three science classes are run by three science teachers who have been introduced to NOS and storytelling during a one-day workshop. These three teachers chose to tell the students a story about Ernest Rutherford. The stories told by the teachers, as well as the whole-class discussions afterwards, are analysed with respect to what NOS aspects were communicated. The results show that many different NOS aspects, such as the tentative nature of scientific models, empirical aspects of the scientific knowledge process, as well as human aspects of science, emerge in the context of the story about Rutherford and his work on the atomic model. The results indicate promising possibilities for storytelling as an approach to NOS teaching.